Evaluation of the Possibility for Using Polypropylene/Graphene Composite as Bipolar Plate Material Instead of Polypropylene/Graphite Composite - Onyu, Kannika; Yeetsorn, Rungsima; Fowler, Michael; Yu, Aiping; Seok Jun, Yun; Prapainainar, Chaiwat; Prissanaroon-Ouajai, Walaiporn (Applied Science and Engineering Progress, 2016)
To reduce the bipolar plate weight and keep the desired power density of a low temperature fuel cell, thermoplastic composite bipolar plates have been fabricated for low temperature fuel cell applications. Concerns over material weight, electrical conductivity, mechanical properties, and injection processability of the thermoplastic nanocomposites have brought forth the idea of producing a polypropylene/graphene nanocomposite for an injection moulded bipolar plate application. In this article, the properties of produced polypropylene/graphene nanocomposites were also compared with the properties of polypropylene/graphite composites to assess the feasibility for using polypropylene/graphene nanocomposites as a bipolar plate material. The effects of graphene contents and sizes on electrical conductivity and mechanical properties were reported in this work. Moreover, the obtained results were discussed in terms of morphology and state of dispersion and distribution of the graphene within the polypropylene matrix. This work is a preliminary study that offers insight into the material selection and development for low temperature fuel cells toward the ultimate goal of broad commercialization.